2016
DOI: 10.1136/thoraxjnl-2015-207490
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-disordered breathing and daytime postural stability

Abstract: SDB severity, especially the mean nocturnal SpO2 level, is associated with impaired daytime postural stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 36 publications
2
33
1
Order By: Relevance
“…We have shown that there are significant differences between the stabilometric profiles of OSAS patients and controls. These results are coherent with previously published studies which have provided evidence that OSAS patients have poorer balance compared with a control population (12,13). Additionally, we have now shown that this increase in CP displacement amplitude specifically concerns the ML axis.…”
Section: Changes In Posturo-respiratory Coupling In Osassupporting
confidence: 93%
See 2 more Smart Citations
“…We have shown that there are significant differences between the stabilometric profiles of OSAS patients and controls. These results are coherent with previously published studies which have provided evidence that OSAS patients have poorer balance compared with a control population (12,13). Additionally, we have now shown that this increase in CP displacement amplitude specifically concerns the ML axis.…”
Section: Changes In Posturo-respiratory Coupling In Osassupporting
confidence: 93%
“…In particular, its association with intermittent hypoxia and altered sleep quality, the principal factors that lead to co-morbidity, remains purely theoretical. Indeed, though changes in stabilometric parameters have been correlated with sleep deprivation (17) or to profound hypoxia (18), which is not typically observed in studies of OSAS patients (12,13). Additionally, the intermittent hypoxia and altered sleep quality do not explain the hyperextension of the cervical spine and the forward projection of the head (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of this kind of association could be conditioned by diverse aspects, such as the subjective assessment of ESS and DHI (which can be influenced by different factors, i.e. depression) and the poor ESS correlation observed in the literature with objectively measured sleepiness (Chervin and Aldrich, ; Degache et al ., ). Conversely, a positive correlation between gain and mean SaO 2 and a negative correlation between CEYL and mean SaO 2 were found (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…There is also emerging evidence that OSA disturbs balance and gait, potentially increasing the propensity for falls, particularly in older patients. [35][36][37] Falls are a leading cause of injury, disability, and mortality worldwide 38 ; and therefore, OSA therapy may be a potential target to reduce falls risk. Preliminary evidence suggests that OSA therapy may reduce gait instability in OSA.…”
mentioning
confidence: 99%